The Success Criteria of Public Housing Project in Nigeria (International Journal of Built Environment and Sustainability, 2016)
There is no consensus among researchers of what constitutes projects success; every project type may have different success criteria. Identifying project success criteria at the initial stage of a project can contribute to effective utilization of resources. The aim of this study is to establish the criteria for measuring public housing project success in Nigeria. The data collection was carried out in Nigeria by means of structured interviews with ten experts in housing, a pilot survey and questionnaire survey.  A questionnaire survey was carried out in which 550 questionnaires were administered to construction professionals who involve in public housing projects, in order to elicit their perceptions on success criteria for public housing projects. The sample was drawn using purposive sampling method since there is no sample frame of people with experience in public housing. Two hundred and seventy six questionnaires (276) were returned completed representing 50.2% response rate. The data collected were analysed using structural equation modelling technique. The results reveal six criteria for measuring public housing project management success, these are client’s satisfaction, project completed on time, project completed to specified quality standard, absence of disputes, safety, and completion within budget. The results also reveal four criteria for measuring public housing product success which include meeting the project purpose, end users’ satisfaction, environmental impact and aesthetic appearance of the . Understanding the findings of this study by policy makers and project managers can improve effectiveness and efficiency of public housing projects in Nigeria.